The Markovian Queue with Bounded Waiting time - Gavish, Bezalel; Schweitzer, Paul J. (Management Science, 1977)
The single-server queueing system is studied where arrivals are rejected if their waiting plus service times would exceed a fixed amount K. Applications of this model include equipment repair facilities and buffered communication devices with constant discharge rate receiving messages from a high-speed data channel. A procedure for computing the equilibrium behavior is described for the case of random arrivals and arbitrary service time requirements. Detailed analytic results and graphs are given for the case of exponentially distributed service time requirements, including the server utilization, rejection probability, mean time in system, mean server busy period, and the mean and probability density function of the virtual waiting time.